2022
DOI: 10.3390/bioengineering9040159
|View full text |Cite
|
Sign up to set email alerts
|

Densification: Hyaluronan Aggregation in Different Human Organs

Abstract: Hyaluronan (HA) has complex biological roles that have catalyzed clinical interest in several fields of medicine. In this narrative review, we provide an overview of HA aggregation, also called densification, in human organs. The literature suggests that HA aggregation can occur in the liver, eye, lung, kidney, blood vessel, muscle, fascia, skin, pancreatic cancer and malignant melanoma. In all these organs, aggregation of HA leads to an increase in extracellular matrix viscosity, causing stiffness and organ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 99 publications
0
13
0
1
Order By: Relevance
“…Ang II through AT1R could promote the fascial remodeling of these elements and fibrinogenesis up to fibrosis. Indeed, the latter, as reported by Stecco et al, in some organs and tissues as fasciae, may occur as a direct consequence of HA densification in the long term [ 15 ]. Moreover, Schleip et al [ 1 ] observed that the density of fascial myofibroblasts (MFBs) in human lumbar fascia could be associated with an augmented occurrence of (micro)injuries and related repair processes in the TLF.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ang II through AT1R could promote the fascial remodeling of these elements and fibrinogenesis up to fibrosis. Indeed, the latter, as reported by Stecco et al, in some organs and tissues as fasciae, may occur as a direct consequence of HA densification in the long term [ 15 ]. Moreover, Schleip et al [ 1 ] observed that the density of fascial myofibroblasts (MFBs) in human lumbar fascia could be associated with an augmented occurrence of (micro)injuries and related repair processes in the TLF.…”
Section: Discussionmentioning
confidence: 94%
“…Although recent studies showed that fascial fibroblasts are sensitive to different stimuli, from biochemical [ 12 , 13 ] to biophysical [ 14 ], promoting ECM remodeling, as well as synthetic activity (collagen fibers of type I and III, and hyaluronan). Stecco et al [ 15 ] suggested that fibrosis may occur in different organs as a long-term consequence of hyaluronan densification due to excessive collagen fiber deposition and consequent ECM remodeling, and this mechanism was also found in the deep fascia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…RHAMM is a centrosome- and microtubule-associated protein that is highly expressed before and during mitosis and hence prominent in neoplastic and other hyperproliferative tissues [ 24 ]. Besides the widely distributed CD44, hyaluronan fragments may also activate RHAMM, LYVE-1 (lymphatic vessel endothelial hyaluronan receptor), HARE (hyaluronan-receptor for endocytosis), ICAM-1 (intercellular adhesion molecule 1), layilin, Toll-like receptor 4, and other cell surface receptors which modulate gene expression via signaling pathways [ 23 , 25 ]. Accordingly, hyaluronan binding is critical for morphogenesis, matrix organization, wound repair/regeneration, inflammation, and metastasis [ 23 ].…”
Section: Hyaluronan Biochemistry Cellular Synthesis and Homeostasismentioning
confidence: 99%
“…It was shown that hyaluronan degradation occurs at pH < 4 and pH > 11 [ 111 ]. Alterations in hyaluronan function may result from the effects of van der Waals and hydrophobic forces on its concentration, polyelectrolyte properties, and aggregation characteristics [ 25 , 108 ]. Hyaluronan takes on non-Newtonian characteristics and becomes more viscous at higher concentrations [ 112 ].…”
Section: The Etiological Significance Of Changes In Hyaluronan Proper...mentioning
confidence: 99%
See 1 more Smart Citation